'Twenty syndrome' in neuromyelitis optica spectrum disorder. Issue 9 (13th September 2020) - Ghosh, Ritwik; Dubey, Souvik; Chatterjee, Subhankar; Lahiri, Durjoy
Abstract : A 30-year-old woman presented with recurrent hiccups, vomiting and painful diminution of vision and gait instability for 1 day. She had one-and-a-half syndrome, bilateral seventh cranial nerve paresis with bilateral symptomatic optic neuritis and left-sided ataxic haemiparesis. We described her disorder as the 'twenty syndrome' (1 1 /2 +7+7+2+2+½=20). MRI of her brain revealed demyelination predominantly in right posterolateral aspect of pons, medulla and bilateral optic nerves. Serum antiaquaporin-4 antibody came out positive. Thus, she was diagnosed as neuromyelitis optica spectrum disorder (NMOSD). She responded brilliantly to immunosuppressive therapy. This is the first ever reported case of the 'twenty syndrome' secondary to cerebral NMOSD.